EdTech in Indonesia : Ready for Take-off? - Bhardwaj, Riaz; Yarrow, Noah; Cali, Massimiliano (World Bank, Washington, DC, 2020)
This EdTech landscape survey provides an overview of the Indonesian startup ecosystem in EdTech, drawing upon three main sources of information: publicly available data, information collected via an online-questionnaire sent to 60 EdTech players—representing the vast majority of the main players—and 18 structured, in-depth face-to-face interviews from December 2018 through February 2019, as well as a group consultation with preliminary findings and recommendations. The findings reveal that the Indonesian EdTech sector is starting to catch up with the global frontier, and with growth of similar platforms, such as Harukaedu (a platform offering online university degrees), Ruangguru (an interactive e-learning platform for K-12 students in Indonesia) and Cakap by Squline (a tutoring platform for language learning), but overall the sector is still in its infancy. This early stage of development applies to evidence as well; there is almost no rigorous information available about the quality or effectiveness of the products and services offered in the Indonesian EdTech market, something that is true of many EdTech markets globally. Indonesian EdTech products generally aim at helping students with learning and upskilling, helping educators with student management, communication and teaching, and helping educational institutions with administration. For example, companies such as Ruangguru, Zenius and Quipper provide self-directed e-learning content, interactive learning platforms, and study tools that help students to expedite the learning process, along with interactive online services that help students with theirassignments and test preparation. Companies such as Arsa Kids, Digikids and Educa Studio develop gamebased and blended learning experiences, including interactive storybooks and educational mobile apps, to help improve early childhood educators' effectiveness.